Influence of maternal age on the birthweight of infants delivered from frozen-thawed blastocyst transfer cycles - Wang, Xue; Xiao, YaLing; Tao, Tao; Xiong, Wei (Frontiers in Endocrinology, 2023)
The aim of this study was to investigate whether maternal age has an effect on the birthweight of singletons delivered from frozen-thawed blastocyst transfer (FBT) cycles. A total of 1203 FBT cycles occurring between July 2011 and June 2021 at a single centre were retrospectively analysed. Based on the maternal age at FBT, the patients were divided into four groups: <30, 30–34, 3537, and ≥38 years of age. Main outcomes measured included singleton birthweights, preterm births, lznc arge-for-gestational-age (LGA) and small-for-gestational-age (SGA) live births among the age groups. There was no significant difference in birth weight among the four groups, while the highest birth weight was found in the <30 years group. The incidence of very preterm births and very low birth weights demonstrated an increasing trend with age; on the contrary, the incidence of preterm births, low birth weight (LBW), high birth weight and LGA and SGA live births gradually decreased with increasing age, but these differences were not statistically significant among groups (P>0.05, respectively). Although the proportion of females was lower than that of males, the difference was not statistically significant among the groups. After adjusting for possible confounders, maternal age was found to have no effect on adverse neonatal outcomes in the regression analyses (P>0.05). Birthweight in singleton births from blastocyst transfers was not affected by maternal age.